Social Media Marketing and Consumer Buying Behavior - Joshi, Chahana; Sejuwal, Narendra; Panta, Sagar; Niroula, Arjun Kumar (International Journal of Atharva, 2025)
This study examines the social media marketing on consumer buying behavior, with a focus on the associations between age, gender, employment, and purchasing decisions. Social media platforms have emerged as powerful tools influencing consumer choices, shaping preferences, and driving brand engagement. The research employs a descriptive, correlational, and quantitative design to assess how individuals across different demographics perceive and respond to social media marketing strategies. The study was conducted in Kathmandu with a sample of 202 participants selected using a convenience sampling technique. Findings from demographic analysis reveal that Instagram and Facebook are the most widely used platforms, with 91.1% of respondents acknowledging social media’s role in discovering products and services. Additionally, 98.5% of participants follow brands on social media, primarily for product updates (23.8%) and exclusive discounts (36.1%). A significant proportion (61.9%) anticipates that social media marketing will evolve further in the coming years. Chi-square analysis was employed to assess associations between age, gender, and employment with consumer buying behavior. The results indicate no statistically significant relationship (p > 0.05) between these demographic factors and purchasing decisions, suggesting that social media marketing influences all consumer segments similarly. This research contributes to understanding the growing role of social media in shaping consumer behavior and provides insights for marketers to tailor digital strategies effectively. Future studies can explore longitudinal trends and qualitative perspectives to deepen insights into evolving social media marketing dynamics.